Problem-Based Learning (PBL) Model Assisted by E-Booklet to Improve Students' Critical Thinking Skills on Environmental Change Material - Nanang Kurniawan; Novianti Muspiroh (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2023)
The study aimed to analyze the difference in improving critical thinking skills between students who applied with the Problem-Based Learning (PBL) model assisted by E-Booklet and those who did not applied with the Problem-Based Learning (PBL) model assisted by E-Booklet. This research was conducted in an Islamic School in Cirebon City with a Quasi-Experimental design in the form of a Pretest-Posttest Control Group Design. Sampling using the Positive Random Sampling technique with a sample size of 64 students. Data collection techniques in the form of essay instrument tests, as many as six questions, with Bloom's taxonomy levels C4-C6 declared valid and reliable. The data analysis technique consists of the N-Gain Test and Statistical Test in the form of a normality test, a homogeneity test, and hypothesis testing with the Mann-Whitney U test. The results showed that the average N-Gain in the experimental class and control class fell into the moderate category, with the acquisition of an average index of 0.61 and 0.47. In the hypothesis test, the experimental and control classes were stated with a significance value of 0.001 ≤ 0.05, meaning Ho is rejected and Ha is accepted. It can be concluded that the application of the Problem-Based Learning (PBL) model assisted by an E-Booklet in learning biology on environmental change material can improve students' critical thinking skills.